Quantification of atrial tachyarrhythmia burden with an implantable pacemaker before and after pulmonary vein isolation. - Pürerfellner H; Aichinger J; Martinek M; Nesser HJ; Ziegler P; Koehler J; Warman E; Hettrick D (Pacing & Clinical Electrophysiology, 2004)
Long-term efficacy of pulmonary vein (PV) ostial isolation for paroxysmal atrial fibrillation is difficult to assess. We evaluated the net duration of atrial tachyarrhythmia episodes (burden), atrial tachyarrhythmia episode frequency, and quality-of-life (QOL) before and after PV isolation in patients with an existing pacemaker featuring extensive diagnostic capabilities. Due to frequent recurrences of paroxysmal atrial fibrillation, PV isolation was performed 21 +/- 10 months following pacemaker implantation on 12 patients (57 +/- 5 years) with normal left ventricular function. Atrial tachyarrhythmia burden (ATB) and episode frequency were monitored daily by the device both pre- and postablation. QOL questionnaires were collected at ablation and 1, 3, and 6 months thereafter. Patients were followed for 20 +/- 9 and 11 +/- 9 months pre- and postablation, respectively. Membrane-active antiarrhythmic medications were discontinued after ablation in 8 of 12 patients. PV isolation resulted in a significant reduction of ATB from a median of 3.2 hours/day (preablation) to 0.2 hours/day (postablation, P < 0.01, Wilcoxon signed-rank test). The median tachyarrhythmia frequency was 6.4 episodes/day (preablation) and 0.3 episodes/day (postablation, P = 0.09). QOL measures significantly improved over the data collection intervals (P < 0.05). Tachyarrhythmia burden was positively associated with Symptom Checklist frequency and severity (P < 0.01). Significant long-term reductions in total ATB (symptomatic and asymptomatic) were observed. Furthermore, reductions in ATB were associated with improvements in QOL measures. Extensive monitoring capabilities in implantable devices help provide complete disclosure on the effect of PV isolation in paroxysmal atrial fibrillation patients.